Contribution of Islamic Banks in the Development of the Halal Industry in South Sulawesi - Arsyad, Kamaruddin; Gani, Ilham; Haliding, Safri (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
Islamic banking can play a significant role in developing the halal industry in South Sulawesi. This study examines the strategies for developing the halal industry through Islamic banking financing models and the support of the local government in South Sulawesi. The study uses field research and secondary data to collect information from Islamic banks, the South Sulawesi Provincial Government, halal industry business players, and the community. The findings show that the halal industry in South Sulawesi is experiencing positive growth. The Provincial Government supports the halal industry by providing a free halal certification program for small and medium enterprises (SMEs) and small and medium industries (IKM). However, Islamic banking does not directly provide financing to the halal industry. The study recommends the following models for distributing halal industry financing: community-based distribution, Islamic boarding school-based distribution, mosque-based distribution, and MSME distribution guided by the government, institutions, State-owned enterprises (BUMN), and Regional-owned enterprises (BUMD).